English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-05-30 08:23:50 · 10 answers · asked by A 1 in Science & Mathematics Mathematics

10 answers

(4x/3) - (x-6) = 7/2

(8x/6) - (x/6) = 7/2 *This is probably what stumped you. you just need to get a common denominator, 6 in this case. It's just like any other fraction.

(7x/6) = 7/2

14x = 42

x=3

2007-05-30 08:26:09 · answer #1 · answered by de4th 4 · 0 0

Since all these numbers are in fractions, the best way to start is to convert everything so that the denominator is the same.

The three denominators are:
4x/3 is 3
x/6 is 6
7/2 is 2
The common multiple between these three numbers is 6, so multiply each number by the correct factor to get the same denominator. If you multiply the bottom number, you must also multiply the numerator.

(4x/3) * 2 = 8x/6
(x/6) * 1 = x/6
(7/2) *3 = 21/6

The new equation is: 8x/6 - x/6 = 21/6
Reduce: (8x-x)/6 =21/6
This becomes: 7x/6 = 21/6
now multiply the equation by 6 to reduce the fractions into integers:
7x = 21
therefore x=3

check your answer:
4(3)/3 - 3/6 =?
12/3 - 3/6 = ?
24/6 - 3/6 = ?
21/6 = ? divide by 3 which is the common factor between 21 and 6 to get 7/2

2007-05-30 15:35:44 · answer #2 · answered by Jun 1 · 0 0

x=3

2007-05-30 15:30:30 · answer #3 · answered by Yauheniya D 1 · 0 0

rewrite the equation in terms of the least common denominator (6)

4x/3 * (2/2) = 8x/6
x/6 * (1/1) = x/6
7/2 * (3/3) - 21/6

8x/6 - x/6 = 21/6

Combine like terms:
7x/6=21/6

Multiply both sides by 6:
7x=21

Divide both sides by 7:
x=3

check your work:
4*3/3 - 3/6 = 7/2
4 - 1/2 = 7/2

7/2 = 7/2 (check)

2007-05-30 15:34:20 · answer #4 · answered by Dave B. 4 · 0 0

get a common denominator on the right side.
It is six.
Multiply 4x/3 by 2/2 to get 8x/6-x/6
7x/6 = 7/2
Multiply both sides of the equation 6 to remove the fractions.
7x= 21
Solve.
x=3

2007-05-30 15:28:39 · answer #5 · answered by random person 4 · 0 0

You need to find the lowest common denominator (of 3, 6 &2). Take that number and multiply each component of the equation by it (4x/3 x L.C.D - x/6 x L.C.D. = 7/2 x L.C.D.) Then you simply add all your "x"s and divided the number on the other of the = sign by your number of xs.

2007-05-30 15:34:47 · answer #6 · answered by whobeme021 4 · 0 0

4x/3-x/6=7/2 multiply all by 6
8x-x=21
7x=21
x=3

2007-05-30 15:28:45 · answer #7 · answered by Anonymous · 0 0

4x/3 - x/6 = 7/2
8x-6 -x/6 = 21/6
7x/6 = 21/6
7x = 21
x = 3

2007-05-30 15:32:15 · answer #8 · answered by ironduke8159 7 · 0 0

4x/3-x/6=7/2


24x-3x
---------------=7/2
18


21x/18 = 7/2


21x=63
x=3

2007-05-30 15:30:03 · answer #9 · answered by ajju_kwt 1 · 0 0

8x - x = 21
7x = 21
x = 3

2007-05-31 08:06:25 · answer #10 · answered by Como 7 · 0 0

fedest.com, questions and answers